2014
DOI: 10.1002/2013jc009548
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Kuroshio transport by mesoscale eddies at the Luzon Strait entrance

Abstract: Measurements of Kuroshio Current velocity at the entrance to Luzon Strait along 18.75 N were made with an array of six moorings during June 2012 to June 2013. Strong positive relative vorticity of the order of the planetary vorticity f was observed on the western flank of the Kuroshio in the upper 150 m. On the eastern flank, the negative vorticity observed was about an order of magnitude smaller than f. Kuroshio transport near its origin is computed from direct measurements for the first time. Kuroshio transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 40 publications
(89 reference statements)
8
90
0
Order By: Relevance
“…Rather, we concentrate on the relationship between the Kuroshio transport and the SSH gradient. Lien et al [2014] found that the Kuroshio transport anomaly is well correlated with the zonal gradient of SSHa at 18.75 N along a transect northeast of Luzon Island. Their observation confirms that the satellite SSHa well reflects the baroclinic structure of Kuroshio [Guinehut et al, 2009] and can be used to provide a measure of the Kuroshio transport northeast of Luzon Island.…”
Section: 1002/2014jc010614mentioning
confidence: 90%
See 2 more Smart Citations
“…Rather, we concentrate on the relationship between the Kuroshio transport and the SSH gradient. Lien et al [2014] found that the Kuroshio transport anomaly is well correlated with the zonal gradient of SSHa at 18.75 N along a transect northeast of Luzon Island. Their observation confirms that the satellite SSHa well reflects the baroclinic structure of Kuroshio [Guinehut et al, 2009] and can be used to provide a measure of the Kuroshio transport northeast of Luzon Island.…”
Section: 1002/2014jc010614mentioning
confidence: 90%
“…The Kuroshio transport or its anomaly is often related with the zonal gradient of sea surface height (SSH) or SSHa [e.g., Lien et al, 2014]. Figure 9 shows time series of the SSH, SSHa, and zonal gradient of SSH along 23.75 N from August 2012 to September 2014.…”
Section: 1002/2014jc010614mentioning
confidence: 99%
See 1 more Smart Citation
“…The former measures both the geostrophic and ageostrophic components of the current; whereas only the absolute geostrophic current is derived from PIES. Some of the periods of large discrepancies between the two volume transport time series may be associated with the mesoscale eddy-Kuroshio interactions reported in Lien et al (2014), as in June, July, and December 2012, while some others seem unrelated to such influence (August-September 2012). The detailed analysis of the differences between ADCPand PIES-derived transports is the subject of an ongoing study.…”
Section: Discrepancies Between Adcp-and Pies-derived Transportsmentioning
confidence: 94%
“…8b). In this case, transports are for the layer between the surface and 600 dbar, following Lien et al (2014), who extrapolate their ADCP measurements to these levels in order to capture a larger part of the Kuroshio transport. In both comparisons, the zonal integration range is set to 122.108-122.878E, which corresponds to the zonal extent of the ADCP array.…”
Section: Absolute Volume Transportmentioning
confidence: 99%